Neuraminidase inhibitor treatment is associated with decreased mortality in COVID-19 patients: a retrospective analysis - Wu, Junfang; Zhao, Mingming; Wei, Haoran; Li, Chenze; Hu, Dong; Zheng, Lemin; Wang, Dao Wen (European heart journal. Cardiovascular pharmacotherapy, 2022)
Abstract Aims The aim of this study was to investigate the effects of Neuraminidase inhibitors (NI) on COVID-19 in a retrospective study. Methods and results The study included an overall COVID-19 patients (n = 3267) and a 1:1 propensity score-matched patients (n = 972). The levels of plasma N-acetylneuraminic acid and neuraminidase expression were further evaluated in a panel of hospitalized and 1-month post-infection recovered COVID-19 subjects. The mortality rate in the overall patients was 9.6% (313/3267) and 9.2% (89/972) in the propensity-score matched patients. The NI treatment lowered the mortality rate (5.7% vs. 10.3%) and the critically ill conversion rate (14.1% vs. 19.7%) compare to those in the non-NI group in the overall patients and evaluated in the propensity score-matched patients when applying the multivariate Cox model for adjusting imbalanced confounding factors. Furthermore, NI treatment was associated with attenuated cytokine storm levels and acute heart injury but not liver or kidney injuries. Further analysis in a small panel of patients found the levels of N-acetylneuraminic acid and neuraminidase (dominantly the NEU3 isoform) were elevated in the hospitalized COVID-19 subjects and recovered at the 1-month post-infection stage, suggesting increasing desialylation in COVID-19 patients. Conclusion These results suggest that NI treatment is associated with decreased mortality in COVID-19 subjects, especially for those subjects with acute heart injury.